Dikes and Dunes: On Dutch History and Dutchness - Benjamin Schmidt (BMGN: Low Countries Historical Review, 2018)
This essay considers one of the more striking qualities of the historiography of the Netherlands: its attitude vis-à-vis outsiders. On the one hand, there is a comparative bent in the scholarship and an interest in seeing the Dutch in the world; in this sense, it is an admirably outward-looking historiography. On the other hand, there is a tendency to underscore the exceptional Dutchness of Dutch history, which encourages analyses to turn inward. Comparativism thus vies with a provincialism, which can devolve into parochialism.